Pengenalan dan Pemberdayaan E-Commerce Pada UMKM Kerupuk Kaisar di Desa Sumberrejo Kabupaten Pasuruan - Elvin Syah Huzaimi; Fatchur Rozci (Jurnal Informasi Pengabdian Masyarakat, 2023)
The use of e-commerce in Ms. Wati's “UMKM Kerupuk Kaisar” marketing can be utilized in their products. E-commerce can be interpreted as a place where trading activities or buying and selling of goods occur which are connected to a network known as the internet network. The “UMKM Kerupuk Kaisar” is one of the businesses located in Sumberrejo Village, Kutjur Hamlet, Purwosari District, Pasuruan Regency. The purpose of introducing and empowering e-commerce is to expand the market and to make products known to the general public. The implementation method used is the learning by doing approach. The result of this e-commerce lesson hoped that the introduction of e-commerce to “UMKM Kerupuk Kaisar” can create a new spirit in doing business so that producers are able to compete with business actors from developed countries.